Pengaruh Pengetahuan Keuangan Terhadap Perencanaan Keuangan Keluarga - Palimbong, Stefani (Aliansi Dosen Perguruan Tinggi Swasta Indonesia (Adpertisi), 2023)
This study aims to determine the effect of financial knowledge on family financial planning. This study used a questionnaire distributed to the community, namely housewives in Lembang Buntu Batu, Rindingallo District, North Toraja Regency with a total sample of 68 respondents. Sampling using non-probability sampling with a purposive sampling approach. The data analysis technique used is simple linear regression analysis. From the test results it is known that Financial Knowledge (X) has a positive and significant effect on Family Financial Planning (Y). In the partial test results it is known that the calculated t value is greater than t table (3.304 > 2.652) and has a small significance value of 0.005 (0.002 <0.005). While the results of the test for the coefficient of determination show that Financial Knowledge (X) has an effect of 62.5% and the remaining 37.5% is influenced by other variables outside of this study. So it can be concluded that financial knowledge has a positive and significant effect on family financial planning.